Análisis del riesgo de crédito de la cartera de microcréditos en la cooperativa “SAC PELILEO LTDA.” sucursal Latacunga durante el período abril 2018 a marzo 2019. - Panchi Lema, Rosa Angelica (2019)
Due to the risky nature of credit activity, credit risk is considered one of the main problems that financial institutions present, making it essential to maintain constant control of this risk, in order to detect future problems with the recovery of these credits, currently financial institutions identify the credit risk of their operations, through the allocation of ratings to their customers, resulting in inadequate control in the granting of credits. Therefore, the main objective of this integrative project was to analyze the risk of the microcredit portfolio in the “SAC Pelileo Ltda.” Cooperative Latacunga branch, estimating the value of loss due to credit risk, during the period April 2018 to March 2019. Then, from a sample of delay data days in payments per customer, adding variables of nominal scale, of reason and interval, through instruments that allowed to apply oriented statistical models to the estimation of probabilities of default (default) and the measurement of Credit Risk in the microcredit portfolio, such as the Probit model, the Credimonitor model and the Credi VaR through the Montecarlo simulation. Therefore, when applying the Montecarlo simulation and obtaining the CrediVaR at a 95% confidence level, the results of the expected, unexpected and catastrophic loss were $ 103,747.50, $ 462.50 and $ 104,210.00 respectively, concluding that the simulation results they are more robust because they are a technique that considers the effects of uncertainty as a fundamental element of risk.